Magnetization reversal modes and coercive field dependence on perpendicular magnetic anisotropy in FePt thin films - Román, A.; Lopez Pedroso, A.; Bouzehouane, K.; Gómez, J.E.; Butera, A.; Aguirre, M.H; Medeiros Soares, M.; García, C.; Steren, L.B. (Purpose-Led Publishing)
Fil: Román, A. Comisión Nacional de Energía Atómica. Instituto de Nanociencia y Nanotecnología; Argentina.